STUDENTS’ AND TEACHERS’ PERSPECTIVE OF ENGLISH LANGUAGE IN MULTILINGUAL EFL CLASSROOM - Yudha Budiman (STKIP PGRI Lubuklinggau, 2020)
Multilingual nowadays become a global phenomenon in which technology growing rapidly and increase people’s mobility from one place to another. Because of the globalized forms of a super diverse society, the identities cannot be identified as well as possible. This research aims to understand the learning system in the English classroom when the teacher explains for students and this study tries to seek the students challenging when the teacher gives the learning use uncommon vocabulary with the student's multilingual background. This study employed diagram statistics, in which questionnaires and interviews were used as the instrument along with qualitative design. Participants in this were 8 students 5 teachers from junior high school in Bogor regency. All students in the sample class were seven until nine grade classrooms.